Optimalisasi Manajemen Persediaan: Strategi Meningkatkan Efisiensi dan Mengurangi Biaya dalam Operasi Rantai Pasokan - Ragil Setyorini; Purwanti (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
Inventory management plays a critical role in ensuring smooth operations in supply chains. Efficient inventory management strategies can help organizations reduce costs, improve customer service, and maintain a balanced flow of goods. This paper explores various techniques for optimizing inventory management, such as Just-in-Time (JIT), Economic Order Quantity (EOQ), and Vendor Managed Inventory (VMI). The study emphasizes the importance of leveraging technology, data analytics, and automation to improve decision-making processes and achieve operational excellence. By adopting the right strategies, businesses can minimize stockouts, reduce excess inventory, and enhance overall supply chain performance.